The Effectiveness Of Use Of E-Learning In Entrepreneurship Courses In Private Vocational School, Pematangsiantar City Preparation - mhd Ramadhan (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
Entrepreneurship learning is also an alternative for students to provide their own attitude and preparation so that they can produce their own jobs. Based on the study of E-learning and problems in the entrepreneurship subject of the Preparatory Private Vocational School, this study aims to determine the effectiveness of the use of E-learning in the entrepreneurship subject of the Preparatory Private Vocational School to improve the learning outcomes of SMK students. This research is expected to be a reference source for teachers and education practitioners to use E-learning media to improve student learning outcomes. The results of this study where XA 0.830, XB 0.865, XC 0.803, and XD 0.919. The results show that the research questionnaire instrument is relevant and the instrument items are declared valid. Analysis of reliability test data is 0.875, which means that greater than 0.70 is said to be reliable (0.875>0.70). It is known that Asymp Sig (2-Tailed) on Shapiro-Wilk XA 0.001, XB 0.017, XC 0.014, and XD 0.003. so that it can be stated that there are two items that are normally distributed, namely XB 0.017 > 0.05, XC 0.014 > 0.05 and there are two items that are not normally distributed, namely XA 0.001 < 0.05, XD 0.003 < 0.05. The e-Learning platform used in this study is the Model Platform. e-learning utilizes distance learning, computer technology and internet networks, where this learning system uses information and communication technology so that students no longer need to be in the classroom to listen.